The Head, The Heart, and Business Virtues - Klein, Sherwin (Journal of business ethics, 2002)
In Section I, I criticize the view, implied by the concept of rational economic man, that feelings are inherently opposed to rationality. I attempt to show that emotions or feelings are essential to the proper functioning of reason, rational objectivity, and practical rationality or rational decision making. In addition, I argue that emotions can help to resolve certain ethical dilemmas. In Section II, I consider business writers who criticize business for overemphasizing the head at the expense of feelings or the heart. In Section III, I discuss the connection between material self-interest (as manifested in trade) – a concept of rational economic man – and business virtues.